(untitled) (Imaginations: Journal of Cross-Cultural Image Studies, 2013)
In Darren Aronofsky’s 2000 film, Requiem for a Dream, based on Hubert Selby Jr.’s 1978 novel, he depicts extreme close-up images of heroin as it cooks, boils, enters a vein, and then passes into the body at the cellular level. The cells sizzle as heroin numbs them. The close-ups and sizzling sounds repeat themselves more and more frequently as our four main characters disintegrate through the process of becoming junkies. These images and others provide vivid, horrific, and exquisite visual renderings of the addiction process, while simultaneously providing stark evidence of heroin’s take-over of the body, mind, and ethical capabilities. The images of heroin’s allencompassing control of the body at its foundational level do not glorify heroin’s power in Aronofsky’s film; these images serve as documents of pure horror. The degradation is devastating, thorough, real, and scarring. Aronofsky describes his film as a monster movie, a modern horror film. And, it is not the type of film in which redemption occurs. The stark and individual solitude of each character at the end of the film cannot be easily penetrated by sobriety or love anytime in the foreseeable future.